Eleanor Roosevelt as a Queer Heroine in Susan Wittig Albert’s Loving Eleanor - Hatice Bay; Alperen Mutlu (HyperCultura, 2025)
Abstract: How might we reimagine Eleanor Roosevelt not only as a political icon but as a figure whose entire life—private and public—queered traditional boundaries of being, sexuality, and power? Susan Wittig Albert presents this possibility in Loving Eleanor (2016), which examines the romantic connection between Lorena Hickok (Hick) and Eleanor Roosevelt (hereafter ER or Eleanor). The novel follows the queer bond and enduring friendship between them through a period from 1928 to 1962, while also depicting Eleanor’s non-traditional relationships with multiple men. Albert’s narrative also demonstrates how ER’s energetic personality interacts with the sociopolitical environment of her time to show her adaptable approach to different social classes, racial and ethnic groups. Through queer theory and Gilles Deleuze and Félix Guattari’s concepts of rhizomatic proliferations, becoming-woman, becomingminoritarian, and other becomings, this essay argues that the fictional Eleanor defies established gender, class, and sexual norms, embracing the ever-evolving and boundless nature of desire, sexuality, and transformation. The analysis reveals how Albert's depiction of ER differs from conventional stories about her to present an unconventional and complex portrait of her character.